2011
DOI: 10.1292/jvms.11-0227
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Tramadol in Dogs Anesthetized with Sevoflurane

Abstract: ABSTRACT. Cardiovascular effects of tramadol were evaluated in dogs anesthetized with sevoflurane. Six beagle dogs were anesthetized twice at 7 days interval. The minimum alveolar concentration (MAC) of sevoflurane was earlier determined in each dog. The dogs were then anesthetized with sevoflurane at 1.3 times of predetermined individual MAC and cardiovascular parameters were evaluated before (baseline) and after an intravenous injection of tramadol (4 mg/kg). The administration of tramadol produced a transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
(36 reference statements)
2
14
0
1
Order By: Relevance
“…Giorgi et al [6] reported that the minimum effective plasma concentration of tramadol as calculated for humans had been maintained for about 6-7 hr following a single IV administration of 4 mg/kg tramadol in dogs. We previously reported [10] that the plasma concentration of tramadol gradually decreased over time from approximately 2,000 ng/ml at 5 min to 500 ng/ml at 120 min after a single IV dose of 4 mg/kg tramadol in older dogs (8-10 years old) anesthetized with sevoflurane 1.3 MAC. In these dogs, the plasma concentration of M1 showed a peak (332 ng/ml) at 15 min and then gradually decreased to approximately 200 ng/ml at 120 min after the tramadol administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giorgi et al [6] reported that the minimum effective plasma concentration of tramadol as calculated for humans had been maintained for about 6-7 hr following a single IV administration of 4 mg/kg tramadol in dogs. We previously reported [10] that the plasma concentration of tramadol gradually decreased over time from approximately 2,000 ng/ml at 5 min to 500 ng/ml at 120 min after a single IV dose of 4 mg/kg tramadol in older dogs (8-10 years old) anesthetized with sevoflurane 1.3 MAC. In these dogs, the plasma concentration of M1 showed a peak (332 ng/ml) at 15 min and then gradually decreased to approximately 200 ng/ml at 120 min after the tramadol administration.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be remembered that sevoflurane causes dose-dependent hypotension, hypoventilation, impaired cardiac contractility and hypothermia in dogs [27]. On the other hand, it has been reported that tramadol is a mild myocardial depressant in dogs anesthetized with sevoflurane [10]. A sparing effect on anesthetic requirement provided by the preemptive administration of tramadol is expected to convey the advantage of preserving cardiovascular function in patients anesthetized with sevoflurane.…”
mentioning
confidence: 99%
“…Several studies have evaluated the effect of drugs combinations administered by continuous IV infusion on the requirement for inhalational agents. Studies with sevoflurane have obtained different basal MAC: 2.2-2.3 vol% (Matsubara et al 2009, Columbano et al 2012) and 1.82-1.9 vol% (Wilson et al 2008, Itami et al 2011, Itami et al 2013, Moran-Muñoz et al 2014. This variation may be due to methodological differences, since various stimuli can be applied, such as electrical stimulation, surgical incisions, digital pressure, tail clamping or movement of the endotracheal tube (Ebert & Schmid 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is capable of providing analgesia and muscle relaxation in the retroumbilical region (SOUZA et al, 2013) and causes minimal cardiorespiratory changes. It also improves control over postoperative pain, reduces transoperative stress (ALBUQUERQUE et al, 2010), is safe and efficient, and can reduce the concentration of inhaled anesthetic required for the maintenance of proper anesthesia (VALVERDE, 2008;ITAMI et al, 2011;BOSMANS et al, 2011;NATALINI et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Epidural morphine, fentanyl, methadone, and tramadol are commonly administered. Tramadol is an atypical opiate, which in addition to binding to the opioid receptors, inhibits the reuptake of norepinephrine and serotonin (GUEDES et al, 2002;BASSO et al, 2008;BORGES et al, 2008;MCMILLAN et al, 2008;SILVA et al, 2008;ITAMI et al, 2011). It also exhibits local anesthetic action by blocking the sodium channels in nociceptive C fibers and A-delta (BASSO et al, 2008;KARGI et al, 2008).…”
Section: Introductionmentioning
confidence: 99%